Indonesia's Policies and Strategies for Embracing Inclusive and Environmentally Friendly Recovery - Asti Sri Purniyati (Journal of World Science, 2025)
The COVID-19 pandemic has significantly impacted various aspects of life, including economic, social, and environmental dimensions. In Indonesia, post-pandemic recovery challenges encompass the need for inclusive and sustainable economic recovery while maintaining ecological sustainability. This research aims to analyze the policies and strategies implemented by Indonesia to achieve a truly inclusive and environmentally friendly recovery after the COVID-19 pandemic. Utilizing a literature study method with a qualitative approach, the data was collected from statutory regulations, books, scientific journals, and other legal sources. Data analysis involved data reduction, presentation, and conclusion drawing. The results indicate that Indonesia has adopted several innovative policies and strategies to promote an inclusive and environmentally friendly recovery, such as the National Economic Recovery Policy Strategy (PEN), diversification of exports, and initiatives aimed at enhancing productivity while ensuring environmental protection. However, the novelty of this research lies in identifying how these strategies uniquely integrate social equity and environmental stewardship in a post-pandemic context, contrasting with previous recovery frameworks. By highlighting the interplay between economic policies and social inclusion, this research contributes to a deeper understanding of sustainable development pathways in Indonesia.